2016
DOI: 10.1007/s13277-016-5405-3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microRNAs in HER2 signaling and trastuzumab treatment

Abstract: The prognostic value of HER2 has been demonstrated in many human cancer types such us breast cancer, gastric cancer and ovarian cancer. Trastuzumab is the first anti-HER2 monoclonal antibody that has remarkably improved outcomes of patients with HER2-positive breast cancer. For HER2-positive metastatic gastric cancers, the addition of trastuzumab to traditional chemotherapy also significantly prolonged overall survival. However, intrinsic and acquired resistance to trastuzumab is common and results in disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…In particular, the key biological functions of lncRNA to malignancies are possibly oncogenic or tumor suppressive mediated by microRNAs (miRNAs). 2,25 This hypothesis provides a theoretical basis for developing a new treatment of malignancies. By intentionally downregulating lncRNAs, tumor progression or cell growth could be inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the key biological functions of lncRNA to malignancies are possibly oncogenic or tumor suppressive mediated by microRNAs (miRNAs). 2,25 This hypothesis provides a theoretical basis for developing a new treatment of malignancies. By intentionally downregulating lncRNAs, tumor progression or cell growth could be inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have suggested that activation of alternative tyrosine kinase receptors (such as EGFR, HER3, FGFR2 and MET) or signaling pathways (such as Src and Notch1), often leading to epithelial-mesenchymal transition, could lead to secondary resistance to trastuzumab [ 27 ]. Micro RNAs have also been pointed out as a potential actor in primary and secondary resistance to HER2-targetting therapy [ 28 ]. Moreover, the direct loss of HER2 overexpression or amplification have been reported after exposition to trastuzumab containing therapy [ 29 , 30 ], raising the question of the interest of new biopsies at disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a promising strategy for breast cancer is the development of novel therapeutic targets, many of which have been studied extensively in preclinical and clinical models [ 2 ]. Trastuzumab, for example, is the first anti-HER2 (human epidermal growth factor receptor 2) monoclonal antibody applied in systemic adjuvant therapy for patients with HER2-positive breast cancer, with significant benefits in BC treatment [ 3 ]. Therefore, the identification of the molecular markers for prognosis is important in benefiting BC patients.…”
Section: Introductionmentioning
confidence: 99%